ANALISIS SISTEM ANTRIAN TIKET TRANS JOGJA DI TERMINAL JOMBOR YOGYAKARTA - Maharsa Pradityatama; Pramudi Arsiwi; Dony Satriyo Nugroho (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2026)
This study analyzes and simulates the ticket queue system of the Trans Jogja Bus Rapid Transit (BRT) at Jombor Terminal, Yogyakarta. Increasing passenger mobility and the growing demand for public transportation services have contributed to queue congestion during peak operating hours. The queue system operates using a single-channel single-phase model with a First Come First Served (FCFS) discipline. This research aims to evaluate the performance of the existing queue system and validate the simulation model using the trace-driven method. Data were collected through direct observation of 300 passengers, including arrival time and service time data. The simulation process was conducted using the Linear Congruential Generator (LCG) method and analyzed using the Mann-Whitney statistical test. The results show that the simulation model successfully represents the real system, with a service time error of only 0.13% and an arrival time error of 1.58%. Furthermore, the Mann-Whitney test indicates no significant difference between the simulation and the actual system, with probability values greater than α = 0.1. The findings demonstrate that the trace-driven simulation method is effective for modeling queue systems and can be used to support queue service improvement strategies at Trans Jogja shelters.